Opposing tumor-promoting and -suppressive functions of Rictor/mTORC2 Signaling in adult glioma and pediatric SHH medulloblastoma - Akgül, Seçkin; Li, Yinghua; Zheng, Siyuan; Kool, Marcel; Treisman, Daniel M.; Li, Chaoyang; Wang, Yuan; Gröbner, Susanne; Ikenoue, Tsuneo; Shen, Yiping; Camelo-Piragua, Sandra; Tomasek, Gerald; et al. (Cell reports, 2018)
Most human cancers arise from stem and progenitor cells by the sequential accumulation of genetic and epigenetic alterations, while cancer modeling typically requires simultaneous multiple oncogenic events. Here, we show that a single p53 mutation, despite causing no defect in the mouse brain, promoted neural stem and progenitor cells to spontaneously accumulate oncogenic alterations, including loss of multiple chromosomal (chr) regions syntenic to human chr10 containing Pten, forming malignant gliomas with PI3K/Akt activation. Rictor/mTORC2 loss inhibited Akt signaling, greatly delaying and reducing glioma formation by suppressing glioma precursors within the subventricular zone stem cell niche. Rictor/mTORC2 loss delayed timely differentiation of granule cell precursors (GCPs) during cerebellar development, promoting sustained GCP proliferation and medulloblastoma formation, which recapitulated critical features of TP53 mutant sonic hedgehog (SHH) medulloblastomas with GLI2 and/or N-MYC amplification. Our study demonstrates that Rictor/mTORC2 has opposing functions in neural stem cells and GCPs in the adult and the developing brain, promoting malignant gliomas and suppressing SHH-medulloblastoma formation, respectively.